2008
DOI: 10.1007/s11706-009-0001-8
|View full text |Cite
|
Sign up to set email alerts
|

Vacancies as a constitutive element for the design of nanocluster-strengthened ferritic steels

Abstract: The existence of nanoclusters that are thermodynamically stable at elevated temperatures is truly intriguing because of its scientific implications and potential applications. Highly stable nanoclusters have been observed by atom probe tomography in iron-based alloys at temperatures close to 1400°C (0.92T m ) that appear to defy the stability constraints of artificially created nanostructured materials. The~4-nm-diameter Ti-, Y-and Oenriched nanoclusters are identified in the new form of a highly defective mat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
45
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(47 citation statements)
references
References 13 publications
2
45
0
Order By: Relevance
“…This intriguing similarity indicates that the same yielding mechanism is dominated by dislocation slip inside the grains, as manifested by the unaltered lattice strains and the increased intergranular strains/stresses. However, at high temperatures from 750 to 800°C, the onset of yielding is immediately followed by lattice softening as seen from decreased lattice strains; this implies that these grains sustain less and less loads, and the plastic deformation is mediated by grain-boundary activities, although the Y-Ti-O NCs and vacancy-solute interactions retard diffusion 40 . It is also noted that, in response to higher values of plastic deformation, a deformation crossover exists from low-temperature strain hardening to high-temperature strain softening; the crossover temperature lies between 400 and 600°C.…”
Section: Discussionmentioning
confidence: 99%
“…This intriguing similarity indicates that the same yielding mechanism is dominated by dislocation slip inside the grains, as manifested by the unaltered lattice strains and the increased intergranular strains/stresses. However, at high temperatures from 750 to 800°C, the onset of yielding is immediately followed by lattice softening as seen from decreased lattice strains; this implies that these grains sustain less and less loads, and the plastic deformation is mediated by grain-boundary activities, although the Y-Ti-O NCs and vacancy-solute interactions retard diffusion 40 . It is also noted that, in response to higher values of plastic deformation, a deformation crossover exists from low-temperature strain hardening to high-temperature strain softening; the crossover temperature lies between 400 and 600°C.…”
Section: Discussionmentioning
confidence: 99%
“…The 2-nm particles have been observed by atom probe tomography which showed that they are clusters composed of Y, Ti, and O, located both within the grains and at grain boundaries [15]. An example of atom probe tomography study is shown in Fig.…”
Section: Nanoscale Particle Size Distributionmentioning
confidence: 99%
“…Here, by nanoclusters, we mean fine scale particles with less well defined boundaries. Indeed, transmission electron microscopy (TEM) carried out on 14YWT demonstrated highdensity stable nanoclusters with diameters of 2-5 nm, and atom probe tomography indicates that these nanoclusters are distinctly enriched with Ti, O and Y, as compared to the matrix composition [15]. Similarly, atom probe tomography studies on a related 12YWT (with 12 wt.% Cr) revealed stable clusters with a diameter of ∼4 nm [3].…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…The structure and chemistry of the nano-oxide particles in ODS steels have been investigated by using various techniques [2][3][4][5][6][7][8][9][10][11], based on which the commonly proposed mechanism for the formation of nano-oxide particles is that room temperature MA produces a supersaturated solid solution containing Y, Ti and O which decomposes during high temperature consolidation to precipitate nano-oxide particles [1]. A 4 brief review of some key findings that support this mechanism and the remaining uncertainties and limitations of techniques is discussed below.…”
Section: Introductionmentioning
confidence: 99%